Macroeconomic Policy Making, Exchange Rate Adjustment and Current Account Imbalances in Emerging Markets. Issue 3 (August 2015) - Duarte, Pablo; Schnabl, Gunther
Abstract Given a series of crisis events after 2007 the discussion about the adjustment channels of current account imbalances has been revived. We examine the role of exchange rates vs macroeconomic policies as determinants of current accounts for a set of 86 mainly emerging market economies between 1990 and 2013 to identify adjustment channels for global imbalances. We find that nominal exchange rates are not the main determinant of current account positions. Instead, depending on the region, monetary and/or fiscal policies are identified as the main driving force of current accounts. For East Asia and the oil exporting countries sterilization policies, i.e. relatively tight monetary policies, are the main determinants. In contrast for many European periphery countries fiscal policy stances are at the core of current account positions. Only for the Latin American countries does the exchange rate play a significant role as determinant of current account positions.